Melaka International Trade Centre (MITC) and international standard / Norhidayah Othman - Othman, Norhidayah (Faculty of Business and Management, 2010)
Melaka International Trade Centre (MITC) is the centre that offers a wide range of public exhibitions and events attracting more than a million visitors annually. To attract more visitors from local and international, MITC have to achieve an international standard in its business. International standard is important for MITC because it is assigning that their business is accepted globally. Therefore, this study can determine on how far MITC live up to its name as an international trade centre from international perspective. Many parties can get benefit from this study especially MITC itself because it can provide full action in order to improve their achievement towards international standard for future undertaking. Although it seems that their business is able to growth, the company still has to face many barriers in the late years. Most of the reason is because there are many competitors who always seek an international standard in their business to compete with MITC in securing events. Other than that, the Meetings, Incentives, Conventions, and Exhibitions (MICE) industry are growing and MITC should take advantage by giving a proof that their organization can meet the needs from international clients. A strong action needs to be taken in order to achieve the international standard in their business so that MITC willing to penetrate their business worldwide and prosper. In future, MITC should get the enquiries from organizers around the world to bring in events to Melaka and also give the good impact towards Malaysian economy.